Realization of information technology for automated translation from inflectional languages to sign language - Barmak, O. V.; Romanyshyn, S. O. (Visnyk of Vinnytsia Politechnical Institute, 2013)
The article describes the algorithmic implementation of information technology for translation from verbal inflectional languages to sign language. For example infological model of Ukrainian dictionary and sign language, related generalized grammatical constructions for automatic translation are built. The experimental results to verify the effectiveness of the proposed information technology are represented.